Flight performance estimation for eVTOL quadcopter configurations - Miasnikoc, M.; Esaulov, S.; Ilyin, I. (My University, 2021)
The present study attempts to compare flight performance of the most popular eVTOL (electrical Vertical Take-Off and Landing) aerodynamic configurations of our days. This study gives a theoretical evaluation of the possible VTOL design of different configurations with full electric or hybrid power plant aimed at the urban mobility applications. Conventional rotorcraft, quadcopters, tiltrotor and tiltwing aircrafts with open rotors and ducted fans have been considered. Different eVTOL design available structural elements mass distributions were found. Flight performance of the eVTOL with full electric and hybrid power plants is estimated. Power available and required for speed envelope from hover to maximal speed modes are calculated. Optimal specific parameters of fully electric and hybrid power plant elements (batteries, generators, electric motors, etc.) are defined to provide acceptable eVTOL flight performance.